Receptor Tyrosine Kinase Inhibitor Sunitinib as Novel Immunotherapy to Inhibit Myeloid-Derived Suppressor Cells for Treatment of Endometriosis - He, Ying; Hung, Sze Wan; Liang, Bo; Zhang, Ruizhe; Gao, Yating; Chu, Ching Yan; Zhang, Tao; Xu, Hui; Chung, Jacqueline Pui Wah; Wang, Chi Chiu (Frontiers in Immunology, 2021)
Endometriosis is a common, benign and hormone-dependent gynaecological disorder which displays altered immunoinflammatory profiles. Myeloid-derived suppressor cells (MDSCs) escape from immunosurveillance in human and mouse endometriosis model. Receptor tyrosine kinase inhibitor Sunitinib can induce MDSCs apoptosis and suppress progression of cancer, but the effects of it in endometriosis and underlying mechanism is not clear. In this study, we employed animal study of endometriosis model in mice and cell culture of endometrial stromal cell lines derived from women with and without endometrioma for treatment of Sunitinib. We found that Sunitinib significantly decreased the endometriotic lesion size and weight after 1 and 3 weeks treatment; and p-STAT3 activation was inhibited in MDSCs after 1 week of treatment. In the 1st week, Sunitinib specifically increased G-MDSCs population in peritoneal fluid but the isolated CD11b+Ly6G+Ly6Clo MDSCs after Sunitinib treatment were presented as mature polynuclear MDSCs, while the control group as immature mononuclear MDSCs. Importantly, we achieved that Sunitinib differentially suppressed gene expressions of immunosuppressive function and differentiation in peritoneal G-MDSCs. For endometriotic lesions, PPARG gene governing glucose metabolism and fatty acid storage important for development of endometriosis was upregulated. In addition, Sunitinib significantly inhibited proliferation of human endometriotic stromal cells, but not endometrial stromal cells, in a dose dependent manner. In conclusion, Sunitinib inhibited endometriotic lesion by promoting peritoneal fluid MDSCs maturation and inhibiting its immunosuppressive functions. It changed the immune microenvironment and inhibited development of endometriosis. These findings suggest that Sunitinib has potential therapeutic effects as novel immunotherapy to promote MDSCs maturation, differentiation and metabolism for treatment of endometriosis.